Sintering Technology Method and Application - Liu, Malin (IntechOpen, 2018)
Sintering technology is an old and extensive technology in many areas, and it has been used especially in ceramic fabrication. This book covers many fields, for example, the development of different sintering technologies in recent years, such as spark plasma sintering, flash sintering, microwave sintering, reaction and laser sintering, and so on, and also some special ceramic material fabrication methods and applications, such as carbon nanotubes mixed with alumina and zirconia ceramics, pure and doped zirconia, ZnO ceramic varistors, and so on.